Pengaruh Model Discovery Learning Terhadap Aktivitas dan Hasil Belajar Kognitif Peserta Didik - Nurlida Tri Apria Putri; Rini Rita T Marpaung (Universitas Lampung, 2019)
The aim of this research ware to determine the effect of discovery learning on student’s activities and cognitive learning outcomes. The design that being used was the measurement of the experiment by applying Non Equivalent Control Group Design Posttest. The sample of this research were 64 student’s of VIID and VIIF classes that were selected by cluster random sampling technique. The research instrument used pretest-posttest and observation sheets of student’s activities. The activity data were analyzed descriptively, while the learning result analyzed by the Independent Sample t-Test at the 5% of confidence level. The result of the research showed that the pencentage of overall activity was 71,4 which belonged as good criteria. While in the experimental class, student’s cognitive learning outcomes differed significantly from the control class. The average of N-gain values in the experimental class was 0,66 while the control class was 0,30. Therefore, that the discovery learning model had effected on student’s activities and significant to cognitive learning outcomes of student’s. Penelitian ini bertujuan mengetahui pengaruh discovery learning terhadap aktivitas dan hasil belajar kognitif peserta didik. Desain yang digunakan yaitu eksperimen dengan Pretes Postes Non Equivalent Control Group Design. Sampel penelitian adalah peserta didik kelas VIID dan VIIF yang berjumlah 64 orang dan dipilih dengan teknik cluster random sampling. Instrumen penelitian menggunakan lembar pretes-postes dan lembar observasi aktivitas peserta didik. Data aktivitas dianalisis secara deskriptif, sedangkan hasil belajar dianalisis dengan uji Independent Sample t-Test pada taraf kepercayaan 5%. Hasil penelitian menunjukkan persentase rata-rata aktivitas keseluruhan sebesar 71,4 termasuk kriteria baik. Sedangkan hasil belajar kognitif kelas eksperimen berbeda signifikan dengan kelas kontrol. Rata-rata N-gain pada kelas ekperimen sebesar 0,66 sedangkan kelas kontrol sebesar 0,30. Dengan demikian, model discovery learning berpengaruh terhadap aktivitas dan signifikan terhadap hasil belajar kognitif peserta didik.Kata kunci: aktivitas, discovery learning, hasil belajar